Connected - Eckstrom, Nathaniel (Docklands, VIC : JoJo Publishing, 2014)
Nathaniel Eckstrom takes us on a whimsical and sensory journey through this quaint little apartment block, exploring its inhabitants, floor by floor and introducing us to its quirky occupants; each very different, but all surprisingly connected. What is it that links each neighbour to the next?
1 foldout page at rear.
For children.
Keywords: Apartment dwellers -- Juvenile fiction; Apartment houses -- Juvenile fiction; Children's stories; Apartment dwellers -- Pictorial works -- Juvenile fiction; Apartment houses -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Apartment dwellers; Apartment houses; Australian; Picture books for children; Fiction